2010
DOI: 10.4014/jmb.0908.08036
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Raw Materials and Bulking Agents on the Thermophilic Composting Process

Abstract: Three typical biological solid wastes, namely, animal manure, garbage, and sewage sludge, were compared with regard to the composting process and the changes in microbial community structure. The effects of different bulking agents such as rice straw, vermiculite, sawdust, and waste paper were compared in manure compost. The differences in the microbial community were characterized by the quinone profile method. The highest mass reduction was found in garbage composting (56.8%), compared with manure and sludge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 39 publications
0
3
0
1
Order By: Relevance
“…According to literature, compost produced from catering waste, kitchen waste, or produced using home composters, has a wide variation on electrical conductivity (EC) values (from 1 to 10 dS. m -1 ) [2,34,35], but high soluble salt concentrations are more usually found in compost produced from cooked or preserved food [36]. Although, similar composed feedstock was equally incorporated into each composter, compost from AAC showed half EC values of those obtained from EVC and ATC; this could be attributed to a lower salt loss through lixiviation in these last two treatments prototypes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to literature, compost produced from catering waste, kitchen waste, or produced using home composters, has a wide variation on electrical conductivity (EC) values (from 1 to 10 dS. m -1 ) [2,34,35], but high soluble salt concentrations are more usually found in compost produced from cooked or preserved food [36]. Although, similar composed feedstock was equally incorporated into each composter, compost from AAC showed half EC values of those obtained from EVC and ATC; this could be attributed to a lower salt loss through lixiviation in these last two treatments prototypes.…”
Section: Resultsmentioning
confidence: 99%
“…This technology has demonstrated to be appropriate to recycle large quantities of organic waste, being technically accessible and reducing environmental impacts of organic waste accumulated without proper control or treatment. Furthermore, waste valorization is accomplished by generating compost, an amendment of high agronomical value [1][2][3]. Particularly, decentralised composting is also an innovative way to involve waste generators as key actors in treatment operations.…”
mentioning
confidence: 99%
“…Como muestra la Figura 7, el contenido de humedad se mantuvo más constante, alrededor de 60% con el tratamiento TC y TB, mientras que el tratamiento control TA durante el proceso de compostaje mostró un endurecimiento de los residuos sobre todo de camote y papa que dificultaron mantener (46,83). Los resultados obtenidos de relación C/N final fueron menores a los obtenidos durante el compostaje de estiércol con paja de arroz (26,6), similares al compostaje de la mezcla lodos y residuos urbanos (13,9) y mayores a los obtenidos al compostaje de residuos urbanos y paja de arroz (11,5) durante 14 días (Tang et al, 2010). Sin embargo, es necesario señalar que, de acuerdo al análisis de varianza, no existen diferencias significativas ni en el modelo ni entre tratamientos en el muestreo final.…”
Section: Contenido De Humedadunclassified
“…Turan et al (2009) reported that expanded vermiculite as an effective additive can reduce the amount of volatile organic compounds during the composting of poultry manure [9]. Tang et al (2010) comparatively characterized the difference in microbial biomass based on a quinone spectroscopy method and the change in bioactivity based on an oxygen consumption method in the composting of three typical biosolid wastes, namely cow manure, food waste, and sewage sludge, under the condition of using vermiculite as a leavening agent and speculated that the microbial biomass rather than the microbial diversity determines the composting activity [10]. Zhang et al (2012) studied the adsorption behavior of fulvic acid (FA) and humic acid (HA) on kaolinite, montmorillonite, and vermiculite, indicating that at higher FA/HA concentrations, the electron transfer from the aromatic unit of FA to the iron cations induces more FA adsorption into vermiculite than HA adsorption, and HA easily accumulates on the surface of these minerals, while FA is more likely to enter the pores of these minerals and block the pores of the minerals than HA [11].…”
Section: Introductionmentioning
confidence: 99%